Analisis Jalan Pahat dan Biaya Produksi Disc Brake Sepeda Motor Menggunakan Metode Taguchi dan Softwate Mastercam - Muhammad Ikhlas; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Tool path generation is very important to optimal time and cost of the production process of product. This research purpose is to analyze tool path generation and production cost of disc brake for roughing and finishing work on die casting product. This research was used the Taguchi method and simulation using by Software Mastercam 2020 (CNC Milling). The simulation result was obtained the estimates time for each variable that was tested. Then it can be analyzed the cost of production to obtaining the efficient tool path in the manufacturing of disc brake. This research was resulted a dynamic tool path in facing with face mill’s tool for roughing process with a spindle speed of 2,825 rpm, the feed rate of 2,373 mm/minute, and depth of cut of 0.18 mm. The contour for roughing process with a spindle speed was 10,743 rpm, the feed rate of 4,673 mm/minute, and depth of cut 0.8 mm. Then the finishing process for facing with end mills’s tool produces a dynamic toolpath with a spindle speed of 11,937 rpm, the feed rate of 8,595 mm/minute, and depth of cut of 0.05 mm. The finishing process for drilling produces a chip break toolpath with a spindle speed was 6,565 rpm and feed rate of 788 mm/minute. Finally the contour for finishing process with a spindle speed was 11,937 rpm, feed rate of 8,595 mm/minute, and depth of cut of 0.25 mm. Therefore, the final simulation was produced 7.2975 minutes for time of production, so the total of production cost was Rp 74,056/product. Keywords : Disc brake, CNC milling, taguchi method, mastercam, cost production